Assessing ecological status in karstic lakes through the integration of phytoplankton functional groups, morphological approach and environmental DNA metabarcoding. (November 2021) - Hanžek, Nikola; Gligora Udovič, Marija; Kajan, Katarina; Borics, Gábor; Várbíró, Gábor; Stoeck, Thorsten; Žutinić, Petar; Orlić, Sandi; Stanković, Igor
Graphical Abstract: Highlights: A comparison of morphology and eDNA-based phytoplankton analysis was performed. The Croatian natural karst lakes were classified in Good or High ecological status. The comparable ecological status between both approaches was presented. Most of the differences in HLPI values were caused by the biomass metric. The 18S rRNA V9 could be suitable for assessing the ecological status of phytoplankton. Abstract: Phytoplankton is one of the key Biological Quality Elements within the Water Framework Directive, used to assess the ecological status of surface water bodies. Water samples for phytoplankton identification were collected from April to September at a total of eight sampling sites in all six Croatian natural karstic lakes with an area greater than 0.5 km 2 . The main objective was to show the comparability of environmental DNA metabarcoding (Illumina sequencing using the hypervariable V9 region of the eukaryotic SSU rRNA gene) with morphologically based assessment and its applicability in assessing the ecological status of lakes. The value of Hungarian lake phytoplankton index (HLPI) indicating the final ecological status was calculated for both datasets using biomass and composition metrics. Chlorophyll a concentration measured using Ultra-High-Performance Liquid Chromatography and Spectrophotometer giving two biomass metrics along with the functional group approach (FG) as the composition metric for the complete taxa/operational taxonomic units (OTUs) lists as well as for the taxa/OTUs that contributed more than 5% to the total biomass/number of amplicons gave four to four HLPI values per sample. HLPI values from both approaches were highly correlated (Pearson's r > 0.92) and classified into good or high ecological status, although different compositions and proportions of FGs were recorded, thus giving the important role to the equal or similar factors assignment to different FGs with similar ecological demands and favourable habitats. In 89% of the samples, HLPI values indicate an equal range of ecological status and most differences were found due to different methods of Chlorophyll a measurement. Different composition metrics between approaches showed significant differences (p < 0.05) only in lakes Prošće and Crniševo. This study showed the applicability of the V9 region of 18S rRNA in ecological status assessment for oligotrophic and mesotrophic lakes due to the comparable results between approaches, but further development and standardization of eDNA metabarcoding are needed for the implementation in routine monitoring programs.